PECULIARITIES OF TEACHING A PROFESSIONAL FOREIGN LANGUAGE IN A CHRISTIAN UNIVERSITY - Шестопалова, Ірина; Синя, Любов (SWorldJournal, 2026)
The article is devoted to the problem of teaching a Foreign Language for Professional Purposes for students of Christian specialties. The article considers the uniqueness of the foreign language learning process in a Christian university, analyses the sp